Narrativas de bloqueio à criminalização da violência contra LGBTIs no Brasil: estudo de caso sobre uma omissão legislativa - De Vitto, Victor Augusto Nunes (Universidade Federal de São Carlos, 2018)
This dissertation aims to analyze the trajectory of the discussions about an anti discrimination law that wanted to include the violence motivated by sexual orientation and gender identity, debates held in the brazilian Congress between 2001 and 2014 within the framework of the process of the bill number 5003 of 2001 and the bill of the Chamber number 122 of 2006, respectively, that intended to amendment to law nº 7716/1989 to equate violence against LGBTIs as a racist hate crime. The main effort of case study was to analyze how the blocking of a political discussion on the historical claim of social movements composed by asexuals, lesbians, gays, bisexuals, transvestites, transsexuals, transgender, intersexuals, queers, pansexuals occurred from the construction of narratives formulated by political actors opposed to the initiative and who mischaracterized the content of the bill, publicly challenged it in civil society and the political class and finally stopped this proceedings in parliament. The Multiple Streams Model provided a normative benchmark to understanding the process of withdrawing a public interest issue from the legislative agenda that could represents a change in the course of the decision making process and may have indicated the state of inaction, or non-decision, of the brazilian state, since it occurred despite the growing cases of violence against these social groups registered in the country. By replicating the concepts and approaching the methodology of John Kingdon, this research was possible by interviews with multiple political actors in favor of a protective measure to LGBTI´s community like legislators, social movement actors and civil society.
Narratives opposed to the criminalization of violence against LGBTIs in Brazil: the case of a parliamentary omission
Keywords: Agenda governamental; Políticas públicas; Modelo dos múltiplos fluxos; LGBTI; PLC 122; Criminalização; Governmental agenda; Public policies; Multiple streams model; LGBTI; PLC 122; Criminalization; Governmental agenda; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS